Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Patterns and Processes in Forest Landscapes
DOI: 10.1007/978-1-4020-8504-8_16
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Sustainable Forestry Initiative in Forest Landscape Changes in Texas, USA

Abstract: We studied the changes in landscape pattern and function resulting from the application of the Sustainable Forestry Initiative (SFI) in East Texas, USA. Changes in landscape structure were studied by comparing landscapes with different management histories. A methodology to integrate landscape and stand pattern dynamics with processes was developed based upon modeling and simulation. The effects of pattern on processes were analyzed with this methodology considering the quality, quantity and configuration of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results of both studies showed that the magnitude of the predicted surface runoff, water yields, and sediment yields at the watershed outlets were generally small, and that the introduction of SMZs resulted in reduced water and sediment yields at the watershed outlets. Similar SFI results using APEX were reported by Azevedo et al (2008).…”
Section: Apex Large Watershed Scenario Applicationssupporting
confidence: 89%
“…The results of both studies showed that the magnitude of the predicted surface runoff, water yields, and sediment yields at the watershed outlets were generally small, and that the introduction of SMZs resulted in reduced water and sediment yields at the watershed outlets. Similar SFI results using APEX were reported by Azevedo et al (2008).…”
Section: Apex Large Watershed Scenario Applicationssupporting
confidence: 89%
“…Respondents to forestry schemes were generally confident that their schemes effectively achieve criteria for biodiversity, soil, water and social aspects. Studies confirm that forest certification improves forest management practices, and habitat suitability and diversity . However, Elbakidze et al still find variations between regions in Sweden and Russia under FSC certification, due to different levels of ambition rather than differences in local conditions (e.g., level of forest fragmentation or land‐use history, cf.…”
Section: Discussion Of Survey Responsesmentioning
confidence: 99%
“…Initiative in the United States, for example, several biodiversity-and water-related processes, criteria, and indicators can only be addressed from a landscape perspective (Azevedo et al 2008). …”
Section: Changes In Forest Managementmentioning
confidence: 99%